Integrasi Pasar Harga Ekspor TSNR (Technically Specified Natural Rubber) Negara ITRC (Sebuah Pendekatan VAR/VECM) - Mutiara Ria Despita Maharani; Alif Hasna Astrima; Irma Riskiana (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
The ITRC countries (Indonesia, Thailand, and Malaysia) are recognized as the leading global producers of TSNR (Technically Specified Natural Rubber). These three countries implement the Agreed Export Tonnage Scheme (AETS) policy to maintain global natural rubber price stability. The effectiveness of the AETS policy depends on the level of market integration by ITRC countries. This research aims to analyze the integration of TSNR export prices among the three countries that are members of the ITRC, specifically Indonesia, Thailand, and Malaysia. The analysis used is model VAR (Vector Autoregressive) or (VECM) Vector Error Correction model. This study employs monthly time series data spanning from January 2007 to December 2023. The data were sourced from the ITC (International Trade Centre) via the public platform trademap.org using HS code (400122). The research variables are TSNR export prices (US) for Indonesia, Thailand, and Malaysia as ITRC members and major TSNR producers in the world. This study also uses the Impulse Response Function (IRF) and Forecast Error Variance Decomposition (FEDV) approaches to obtain more comprehensive findings. The findings indicate that the TSNR export prices of Indonesia, Thailand, and Malaysia are linked in the long run. Nevertheless, in the short run, the three countries are not fully integrated. The FEDV analysis indicates that Malaysia holds a more dominant position in TSNR price movements than Indonesia and Thailand. Therefore, ITRC countries need to strengthen cooperation and information transparency in policy-making and routine evaluation. The practical implication derived from this study is that Indonesia and Malaysia need to strengthen coordination because the TSNR export prices of the two countries have been integrated. However, Thailand needs to adjust its trade policy to achieve the integration of TSNR export prices of ITRC member countries.